2011
DOI: 10.1007/s10803-011-1222-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Predictors of the Social Competence of Adults with Autism

Abstract: Longitudinal research into adult outcomes in autism remains limited. Unlike previous longitudinal examinations of adult outcome in autism, the twenty participants in this study were evaluated across multiple assessments between early childhood (M = 3.9 years) and adulthood (M = 26.6 years). In early childhood, responsiveness to joint attention (RJA), language, and intelligence were assessed. In adulthood, the parents of participants responded to interviews assessing the adaptive functioning, autistic symptomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
119
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 55 publications
8
119
3
1
Order By: Relevance
“…Eaves and Ho (2008) reported somewhat better outcomes in a group of low-to middle-functioning individuals (majority had IQ < 70) with approximately half having fair to good outcome and half poor (but none very poor). Similar outcomes were reported by Gillespie-Lynch et al (2012), with 50% reporting poor outcome and 50% fair to very good outcome. Engstrom, Ekstrom, and Emilsson (2003) reported on the psychosocial functioning of a systematically selected sample of patients with Asperger syndrome (AS) and high-functioning autism (HFA) all of whom had an IQ above 70.…”
Section: Adult Independencesupporting
confidence: 76%
See 3 more Smart Citations
“…Eaves and Ho (2008) reported somewhat better outcomes in a group of low-to middle-functioning individuals (majority had IQ < 70) with approximately half having fair to good outcome and half poor (but none very poor). Similar outcomes were reported by Gillespie-Lynch et al (2012), with 50% reporting poor outcome and 50% fair to very good outcome. Engstrom, Ekstrom, and Emilsson (2003) reported on the psychosocial functioning of a systematically selected sample of patients with Asperger syndrome (AS) and high-functioning autism (HFA) all of whom had an IQ above 70.…”
Section: Adult Independencesupporting
confidence: 76%
“…Intellectual functioning (IQ) and language have been most consistently identified as the best predictor of adult personal independence as outcome in ASD (Billstedt et al 2005(Billstedt et al , 2007Gillberg and Steffenburg 1987;Gillespie-Lynch et al 2012;Howlin et al 2004;Kobayashi et al 1992;Lotter 1974;Nordin and Gillberg 1998;Rumsey et al 1985), although reports have been variable (Farley et al 2009;Gillespie-Lynch et al 2012). Farley et al (2009) reported that early childhood variables were weakly associated with adult outcomes, but the participants in their study all had communicative phrase speech or better language by age 6 and near average to average IQ.…”
Section: Predictors Of Adult Independencementioning
confidence: 93%
See 2 more Smart Citations
“…There is consensus that verbal skills play a critical role in predicting long-term outcomes for children with ASD in areas such as adaptive functioning, psychosocial adjustment and wellbeing (Gillespie-Lynch et al, 2012;Hofvander et al, 2009;Howlin, 2003;Howlin & Moss, 2012;Mawhood & Howlin, 2000;Szatmari, Bryson, Boyle, Streiner, & Duku, 2003). Language skills are also critical to school placements and academic performance as well as the ability to participate in successful social interactions (Thurm, Lord, Lee, & Newschaffer, 2007).…”
Section: Introductionmentioning
confidence: 99%